POE composition and preparation method thereof
By plasma modification of the concave and convex rod soil and blending it with graphene and other components, a POE composition with good flame retardant performance is prepared, which solves the problems of complexity and high cost of the existing flame retardant system, and achieves an environmentally friendly and efficient flame retardant effect.
Patent Information
- Application Number
- CN202311384033.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-24
- Publication Date
- 2025-04-29
AI Technical Summary
The existing flame retardant system has problems such as complex production and manufacturing process, high cost, and large environmental pollution, and the flame retardant performance of POE materials is poor, making it difficult to meet market demand.
The plasma reactor is used to modify the concave and convex rod soil, combined with components such as graphene, silicone oil, chitosan, ammonium polyphosphate, nanomagnesium hydroxide, coupling agent and light stabilizer, to form a POE composition, and blend it through an extruder to prepare a POE material with good flame retardant properties.
The flame retardant performance of POE materials has been significantly improved, production costs have been reduced, process flow has been simplified, and hazards to the environment and human body have been reduced. The heat resistance and physical and mechanical properties of the materials have also been improved.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of flame retardant technology, and in particular to a POE composition with flame retardant performance and a preparation method thereof. Background Art
[0002] Thermoplastic elastomer (POE) is a material obtained by in-situ polymerization of ethylene and α-olefin using metallocene catalysts. POE materials have unique properties due to their unique molecular chain structure and have been widely used in polymer modification, photovoltaic film, auto parts, home appliances and other fields. However, its limiting oxygen index is only 17, which is a flammable material, and the molten drop phenomenon is relatively obvious. Therefore, it is of great significance to improve and enhance the flame retardant properties of POE materials. Compounding POE materials with composite flame retardant materials to make new composite flame retardant materials has great application value. However, some existing flame retardant materials have many products from chemical or petrochemical routes, high production costs, relatively complex ingredients (such as some compounded organic synthetic flame retardants), and are not very environmentally friendly. Although some inorganic flame retardants have good flame retardant effects, they require a large amount of addition (30-50%), and have poor compatibility with polymer materials, making the processing process more complicated; in addition, they have a relatively large impact on the physical and mechanical properties of the material.
[0003] Chinese patent CN201710259973.0 discloses a thermoplastic polyester elastomer flame retardant composition, which includes a thermoplastic polyester elastomer (TPEE) and a monomolecular expandable alkyl phosphinate flame retardant. Based on 100 parts by mass of the TPEE flame retardant composition, the monomolecular expandable alkyl phosphinate is 10 to 40 parts by mass, and the rest is TPEE. The monomolecular expandable alkyl phosphinate is a monomolecular expandable alkyl phosphinate metal salt that integrates an acid source, a carbon source, and a gas source, and the monomolecular expandable alkyl phosphinate contains a carboxylate structure that can produce good compatibility with TPEE. However, there may be problems such as relatively unsatisfactory flame retardant and heat insulation effects and relatively insufficient residual carbon.
[0004] Chinese patent CN 101948581 B discloses an intumescent flame-retardant polyethylene containing an organosilicon compound, wherein the intumescent flame-retardant polyethylene containing an organosilicon compound also contains a metal oxide hydrate of an organosilicon flame retardant synergist, and the contents of each component by weight percentage are: polyethylene 70-80%, compound intumescent flame retardant 17-29.5%, and metal oxide hydrate containing an organosilicon flame retardant synergist 0.5-3%, but the process is relatively complicated.
[0005] Chinese patent CN201910746533.7 uses light-burned magnesium powder as raw material and graphene flakes as templates to in-situ grow hexagonal flaky magnesium hydroxide to form a structure of magnesium hydroxide-coated graphene, and performs in-situ modification of the composite flame retardant to obtain a magnesium hydroxide / graphene flake composite flame retardant; however, the process and preparation requirements are relatively high.
[0006] Chinese patent CN 113717450A discloses a low-smoke halogen-free flame-retardant cable material and a preparation method thereof, which is made of the following raw materials in parts by weight: 100 parts of base resin, 50-80 parts of modified aluminum hydroxide, 50-80 parts of nano magnesium hydroxide, 10-35 parts of ammonium polyphosphate, 1-3 parts of molybdenum trioxide, 15-20 parts of compatibilizer, 0.4-1.8 parts of silicone masterbatch, 1-10 parts of nano clay, 5-7 parts of nano graphene powder, and 0.5-2.8 parts of antioxidant; wherein the base resin is composed of low-density polyethylene, polyolefin elastomer and ethylene-vinyl acetate copolymer resin, and the mass ratio of the low-density polyethylene, the polyolefin elastomer and the ethylene-vinyl acetate copolymer resin is 1-4:1-4:1. The nano clay is any one of montmorillonite, sepiolite, attapulgite and kaolin. However, this technology is used to prepare low-smoke, halogen-free, flame-retardant cable materials. The base materials include low-density polyethylene, polyolefin elastomer and ethylene-vinyl acetate copolymer resin, which is relatively complex and requires a large amount of inorganic flame retardant.
[0007] Chinese patent CN111647265A discloses an oil-resistant, low-smoke, halogen-free, flame-retardant flexible polyurethane cable material and its preparation method, which is composed of the following raw materials in parts by weight: 30-40 parts of thermoplastic polyurethane elastomer, 7-10 parts of polar rubber, 10-15 parts of EPDM rubber, 5-8 parts of polymer compatibilizer, 5-8 parts of terminal isocyanate polyurethane prepolymer, 80-100 parts of inorganic flame retardant, 5-8 parts of phosphorus flame retardant, 14-20 parts of white carbon black, 5-15 parts of mineral filler, 3-7 parts of vulcanization accelerator, 0.5-3 parts of radiation sensitizer, 3-5 parts of antioxidant, 0.2-1.5 parts of coupling agent, 1-2 parts of antistatic agent, and 1-2 parts of calcium stearate. However, this method forms functional inorganic particles with polyurethane as soft shell and filler as hard core through mechanochemical reaction, and the process is relatively complicated.
[0008] The flame retardant properties of existing POE materials are relatively poor, and there is an urgent need to increase the added value of the materials and develop an environmentally friendly, novel flame retardant POE material to broaden the application areas of the product and continuously meet market demand. Summary of the invention
[0009] The purpose of the present invention is to solve some problems existing in the currently commonly used flame retardant systems, such as the complex production process of synthetic flame retardants, high production costs, and greater environmental pollution, and to develop more environmentally friendly, effectively flame-retardant halogen-free green flame retardants, thereby increasing the added value of POE materials, making full use of various natural materials and some industrial wastes, reducing the production cost of flame retardants, and reducing various adverse effects of large-scale polymer combustion on the environment and human body.
[0010] To achieve the above-mentioned purpose, the present invention provides a POE composition, which has flame retardant properties and comprises the following components in parts by weight: 0.5-4 parts of graphene, 10-15 parts of modified attapulgite, 2-5% of the total weight of modified attapulgite and graphene, 8-12 parts of chitosan, 5-10 parts of ammonium polyphosphate, 5-10 parts of nano magnesium hydroxide, 0.5-1 parts of coupling agent, 0.5-2 parts of light stabilizer and 90-140 parts of POE base material.
[0011] The POE composition of the present invention comprises: 0.8-2.5 parts of graphene, 11-14 parts of modified attapulgite, silicone oil (accounting for 2.5-4.0% of the mass ratio of modified attapulgite and graphene), 9-11 parts of chitosan, 6-9 parts of ammonium polyphosphate, 6-9 parts of nano magnesium hydroxide, 0.7-1 parts of coupling agent, 0.9-1.5 parts of light stabilizer and 110-130 parts of POE base material.
[0012] In the POE composition of the present invention, the modified attapulgite is attapulgite treated by plasma modification.
[0013] The POE composition of the present invention, the modified attapulgite is prepared by the following steps: adding attapulgite to a plasma reactor, inputting a treatment gas, and treating the attapulgite by using electrons, free radicals, ions, and excited molecules in the plasma reactor to obtain the modified attapulgite.
[0014] The flame retardant POE composition of the present invention, the processing gas includes but is not limited to at least one of oxygen, nitrogen, argon and methane.
[0015] The POE composition of the present invention has a plasma reactor with a power of 30-100 watts, a treatment time of 10-50 minutes, and a treatment gas flow rate of 20-60 ml / min.
[0016] After the attapulgite is treated with gas, the surface of the attapulgite is rich in active groups, which can improve the surface performance and activity of the attapulgite, enable it to react better with other substances, and promote better combination of flame retardants and POE base materials, thereby achieving the purpose of improving the flame retardant effect. In addition, no chemicals are added in the entire treatment process, and there is no solvent residue afterwards, so the process is simple and easy.
[0017] In the POE composition of the present invention, the coupling agent includes but is not limited to one of silanes, titanates and aluminates.
[0018] The silane coupling agent is, for example but not limited to, at least one of vinyltrichlorosilane, vinyltrimethoxysilane, vinylmethyldichlorosilane, γ-chloropropyltrimethoxysilane, γ-chloropropyltriethoxysilane, γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, and γ-aminoethylaminopropyltrimethoxysilane.
[0019] The titanate coupling agent is, for example but not limited to, at least one of bis(dioctyl pyrophosphate)ethylene titanate, isopropyl tri(isostearoyl) titanate, isopropyl tri(dioctyl pyrophosphate) titanate, isopropyl di(methacryloyl) isostearyl titanate, and isopropyl tri(dodecylbenzenesulfonyl) titanate.
[0020] The aluminate coupling agent is, for example but not limited to, at least one of isopropyl distearate acyloxyaluminate, trimethyl aluminate, triethyl aluminate, and tribenzyl aluminate.
[0021] In the POE composition of the present invention, the organic silicone oil includes but is not limited to at least one of methyl silicone oil, methylethoxy silicone oil, methylvinyl silicone oil, methylhydroxy silicone oil, ethyl hydrogen silicone oil or hydroxy hydrogen silicone oil and methyl hydrogen silicone oil.
[0022] In the POE composition of the present invention, the light stabilizer includes but is not limited to at least one of a benzotriazole light stabilizer, a benzophenone light stabilizer and a triazine light stabilizer.
[0023] The benzotriazole light stabilizer is, for example but not limited to, at least one of 2'-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, and 2-(2'-hydroxy-3',5'-di-tert-amylphenylbenzotriazole.
[0024] The benzophenone light stabilizer is, for example but not limited to, 2-hydroxy-4-n-octyloxybenzophenone.
[0025] The triazine light stabilizer is, for example but not limited to, 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl)-5-octyloxyphenol.
[0026] The POE composition of the present invention is not particularly limited to the performance and type of the POE base material. Preferably, the POE base material has a melt index (MFR) of 5-35 g / 10 min at 190° C. and a load of 2.16 kg, and a density of 0.86-0.91 g / cm 3 The "melt index" of the present invention refers to the value of the POE base material measured by a melt index tester at 190°C and a load of 2.16 kg according to the test standard ASTM D1238.
[0027] The POE composition of the present invention further comprises an antioxidant, wherein the antioxidant is added in an amount of 0.1-3 parts by weight, preferably 0.3-2 parts by weight.
[0028] The present invention does not particularly limit the type of antioxidant, and the antioxidant includes but is not limited to antioxidant 1010, antioxidant 1076, antioxidant 168, antioxidant 626 and compound antioxidants thereof.
[0029] Preferably, the antioxidant is a composite antioxidant, the main antioxidant of the composite antioxidant is antioxidant 1010 or antioxidant 1076, and the auxiliary antioxidant is antioxidant 168 or antioxidant 626; wherein the mass ratio of the main antioxidant to the auxiliary antioxidant is 1:1-1:2, and the mass ratio is, for example but not limited to, 1:1, 1:1.5, 1:2.
[0030] The present invention also discloses a method for preparing a POE composition, which comprises the following steps:
[0031] Step 1: Modify the modified attapulgite and graphene with silicone oil, then add ammonium polyphosphate, chitosan, nano magnesium hydroxide and a coupling agent to mix to obtain a composite flame retardant material matrix;
[0032] Step 2: Add the compounded flame retardant material matrix, light stabilizer, POE base material and antioxidant into an extruder for mixing, and obtain a POE composition after extrusion.
[0033] The preparation method of the POE composition of the present invention can also be described in detail as follows:
[0034] Step 1, preparation of modified attapulgite:
[0035] A plasma reactor is used, at a certain power and treatment time, with oxygen, nitrogen, argon or methane as the treatment gas, and active particles such as electrons, free radicals, ions, and excited molecules in the plasma are used to treat the attapulgite for a certain time to obtain modified attapulgite. The power of the plasma reactor is generally 30-100 watts, the treatment time is 10-50 minutes, and the gas flow rate is 20-60 ml / minute.
[0036] Step 2: Compounding of modified attapulgite and other flame retardants:
[0037] The modified attapulgite (10-15 parts by mass) obtained in step 1 and graphene (0.5-4 parts by mass) are modified with silicone oil (2-5% of the mass ratio of attapulgite and graphene). Then, the modified attapulgite is mixed with ammonium polyphosphate (5-10 parts by mass), chitosan (8-12 parts by mass), nano magnesium hydroxide (5-10 parts by mass), and a coupling agent (0.5-1 parts by mass) to form a composite flame retardant material matrix.
[0038] Step 3, blending of compounded flame retardant material and POE material:
[0039] The compounded flame retardant material obtained in step 4 is added into a twin-screw extruder at a certain temperature for mixing with a light stabilizer (0.5-3 parts by mass), a POE base material (90-140 parts by mass), and an antioxidant (0.1-3 parts by mass), and extruded to obtain a POE composition.
[0040] The present invention makes extensive use of inexpensive attapulgite, has obvious environmental value, and can greatly reduce the production cost of flame-retardant POE materials. The attapulgite can be attapulgite that has been discarded after industrial use and has been simply treated. The preparation method of the present invention effectively reduces the overall production cost of the flame retardant, makes better use of industrial waste and natural materials, and the preparation process is simple and easy to implement. The raw materials do not contain halogens and are more environmentally friendly; it also reduces the adverse effects on the environment and human health under the combustion environment. The present invention modifies attapulgite by plasma, and the surface of the modified attapulgite has relatively abundant active groups such as hydroxyl and carboxyl, which is conducive to the subsequent formation of ultra-high molecular weight polyethylene compositions, and improves the flame retardant properties of the POE composition. Compared with the existing modification technologies such as other organic modified attapulgite and acid modified attapulgite, it has the characteristics of being more environmentally friendly and efficient. The present invention combines graphene, modified attapulgite, silicone oil, chitosan, ammonium polyphosphate, nano magnesium hydroxide, a coupling agent, a light stabilizer, and a POE base material. The components act synergistically, and the heat resistance and flame retardancy of the obtained POE composition are improved, and the generation of molten droplets is effectively suppressed. DETAILED DESCRIPTION
[0041] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Those skilled in the art in this field can make some non-essential improvements and adjustments to the present invention based on the above content of the present invention. The raw materials used in the following examples and comparative examples, unless otherwise specified, are all commercially available.
[0042] Analytical methods
[0043] The limiting oxygen index (LOI) was tested using a LOI instrument (Model 5801, produced by Kunshan Yangyi Testing Instrument Co., Ltd.) using the standard GB / T 2406-2009.
[0044] Raw materials and sources
[0045] Attapulgite, purchased from Xuyi County Zhongcai Attapulgite Clay Co., Ltd., model TS003; graphene, purchased from Jinan Moxi New Material Technology Co., Ltd.; ammonium polyphosphate, purchased from Green Union (Jining) Chemical Technology Co., Ltd., with a purity greater than 98%; chitosan, purchased from Shandong Haiyihua Biotechnology Co., Ltd., with a purity of 90%; nano magnesium hydroxide, purchased from Hangzhou Jikang New Materials Co., Ltd., with a purity of 99.5%; titanate coupling agent, commercially available, industrial product; light stabilizer, commercially available, industrial product; POE base material, purchased from ExxonMobil, Dow, Mitsui, etc.; antioxidants 1010, 1076, 168, 626, purchased from Yingkou Fengguang Chemical Co., Ltd.
[0046] Example 1
[0047] (1) Preparation of modified attapulgite:
[0048] A plasma reactor was used, oxygen was used as the processing gas; the reaction power was 70 watts, the processing time was 45 minutes, and the gas flow rate was 50 ml / minute, to modify the attapulgite to obtain modified attapulgite.
[0049] (2) Compounding of modified attapulgite and other flame retardants:
[0050] 12 parts by mass of the modified attapulgite obtained in step (1) and 2 parts by mass of graphene are modified with 0.7 parts by mass of methyl silicone oil, and then mixed with 10 parts by mass of ammonium polyphosphate, 8 parts by mass of chitosan, 6 parts by mass of nano magnesium hydroxide, and 0.6 parts by mass of titanate coupling agent bis(dioctyloxypyrophosphate)ethylene titanate to obtain a composite flame retardant material matrix.
[0051] (3) Blending of compound flame retardant material matrix and POE base material:
[0052] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 210° C. for granulation, and a flame retardant POE composition is obtained, wherein 1 part by mass of a light stabilizer benzotriazole 2'-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 120 parts by mass of a POE base material, and 0.3 parts by mass of an antioxidant having a ratio of 1:2 between antioxidant 1010 and antioxidant 168.
[0053] The resulting POE composition had a limiting oxygen index (LOI) of 29.
[0054] Example 2
[0055] (1) Preparation of modified attapulgite:
[0056] A plasma reactor was used, nitrogen was used as the processing gas; the reaction power was 80 watts, the processing time was 40 minutes, and the gas flow rate was 20 ml / minute, to modify the attapulgite to obtain modified attapulgite.
[0057] (2) Compounding of modified attapulgite and other flame retardants:
[0058] 10 parts by mass of the modified attapulgite and 1.5 parts by mass of graphene obtained in step (1) are modified with 0.23 parts by mass of methylethoxy silicone oil, and then mixed with 10 parts by mass of ammonium polyphosphate, 10 parts by mass of chitosan, 8 parts by mass of nano magnesium hydroxide, and 0.6 parts by mass of silane coupling agent γ-chloropropyltriethoxysilane to obtain a composite flame retardant material matrix.
[0059] (3) Blending of compound flame retardant material matrix and POE base material:
[0060] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 225° C. for granulation to obtain a flame retardant POE composition, wherein the composite flame retardant material matrix obtained in step (2) is mixed with 130 parts by mass of a POE base material, 1.5 parts by mass of a light stabilizer benzotriazole 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, and 0.3 parts by mass of a composite antioxidant formed by an antioxidant 1010 and an antioxidant 168 in a mass ratio of 1:1.5.
[0061] The resulting POE composition had a limiting oxygen index (LOI) of 30.
[0062] Example 3
[0063] (1) Preparation of modified attapulgite:
[0064] A plasma reactor was used, methane gas was used as the processing gas; the reaction power was 90 watts, the processing time was 50 minutes, and the gas flow rate was 45 ml / minute, to modify the attapulgite to obtain modified attapulgite.
[0065] (2) Compounding of modified attapulgite and other flame retardants:
[0066] 10 parts by mass of the modified attapulgite obtained in step (1) and 2 parts by mass of graphene are modified with 0.36 parts by mass of methylhydroxy silicone oil, and then mixed with 8 parts by mass of ammonium polyphosphate, 10 parts by mass of chitosan, 9 parts by mass of nano magnesium hydroxide, and 0.7 parts by mass of an aluminate coupling agent isopropyl distearate acyloxyaluminate to obtain a composite flame retardant material matrix.
[0067] (3) Blending of compound flame retardant material matrix and POE base material:
[0068] The composite flame retardant material matrix obtained in step (2) and 1 part by mass of light stabilizer benzotriazole 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole, 125 parts by mass of POE base material, and 0.3 parts by mass of a composite antioxidant formed by antioxidant 1010 and antioxidant 626 in a mass ratio of 1:1.5 are added into a twin-screw extruder at 220° C. for granulation to obtain a flame retardant POE composition.
[0069] The resulting POE composition had a limiting oxygen index (LOI) of 30.
[0070] Example 4
[0071] (1) Preparation of modified attapulgite:
[0072] A plasma reactor was used, nitrogen was used as the processing gas; the reaction power was 65 watts, the processing time was 45 minutes, and the gas flow rate was 60 ml / minute to modify the attapulgite to obtain modified attapulgite.
[0073] (2) Compounding of modified attapulgite and other flame retardants:
[0074] 13 parts by mass of the modified attapulgite obtained in step (1) and 2 parts by mass of graphene are modified with 0.3 parts by mass of ethyl hydrogen silicone oil, and then mixed with 10 parts by mass of ammonium polyphosphate, 8 parts by mass of chitosan, 10 parts by mass of nano magnesium hydroxide, and 0.6 parts by mass of titanate coupling agent isopropyl tri(dodecylbenzenesulfonyl) titanate to obtain a composite flame retardant material matrix.
[0075] (3) Blending of compound flame retardant material matrix and POE base material:
[0076] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 220° C. for granulation to obtain a flame retardant POE composition. The composite flame retardant material matrix obtained in step (2) is mixed with 1 part by mass of a light stabilizer 2-hydroxy-4-n-octyloxybenzophenone, 0.5 part by mass of 2'-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 135 parts by mass of a POE base material, and 0.3 part by mass of a composite antioxidant formed by an antioxidant 1076 and an antioxidant 168 in a mass ratio of 1:2.
[0077] The resulting POE composition had a limiting oxygen index (LOI) of 31.
[0078] Example 5
[0079] (1) Preparation of modified attapulgite:
[0080] A plasma reactor was used, argon was used as the processing gas; the reaction power was 65 watts, the processing time was 40 minutes, and the gas flow rate was 60 ml / minute to modify the attapulgite to obtain modified attapulgite.
[0081] (2) Compounding of modified attapulgite and other flame retardants:
[0082] 15 parts by mass of the modified attapulgite obtained in step (1) and 3 parts by mass of graphene are modified with 0.4 parts by mass of methyl vinyl silicone oil, and then mixed with 10 parts by mass of ammonium polyphosphate, 10 parts by mass of chitosan, 8 parts by mass of nano magnesium hydroxide, and 0.8 parts by mass of titanate coupling agent isopropyl tri(isostearoyl) titanate to obtain a composite flame retardant material matrix.
[0083] (3) Blending of compound flame retardant material matrix and POE base material:
[0084] The composite flame retardant material matrix obtained in step (2) and 0.3 parts by mass of a composite antioxidant formed by light stabilizer 2-hydroxy-4-octyloxybenzophenone, 110 parts by mass of POE base material, and antioxidant 1010 and antioxidant 626 in a mass ratio of 1:1 are added to a twin-screw extruder at 230° C. for granulation to obtain a flame retardant POE composition.
[0085] The resulting POE composition had a limiting oxygen index (LOI) of 29.
[0086] Example 6
[0087] (1) Preparation of modified attapulgite:
[0088] A plasma reactor was used, nitrogen was used as the processing gas; the reaction power was 70 watts, the processing time was 50 minutes, and the gas flow rate was 45 ml / minute to modify the attapulgite to obtain modified attapulgite.
[0089] (2) Compounding of modified attapulgite and other flame retardants:
[0090] 12 parts by mass of the modified attapulgite obtained in step (1) and 3 parts by mass of graphene are modified with 0.3 parts by mass of ethyl hydrogen silicone oil, and then mixed with 10 parts by mass of ammonium polyphosphate, 9 parts by mass of chitosan, 8 parts by mass of nano magnesium hydroxide, and 0.8 parts by mass of silane coupling agent γ-aminoethylaminopropyltrimethoxysilane to obtain a composite flame retardant material matrix.
[0091] (3) Blending of compound flame retardant material matrix and POE base material:
[0092] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 215° C. for granulation to obtain a flame retardant POE composition. 1.6 parts by mass of light stabilizer 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 135 parts by mass of POE base material, and 0.3 parts by mass of a composite antioxidant formed by antioxidant 1010 and antioxidant 168 in a mass ratio of 1:2 are added to the composite flame retardant material matrix obtained in step (2), 1.6 parts by mass of light stabilizer 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 135 parts by mass of POE base material, and 0.3 parts by mass of a composite antioxidant formed by antioxidant 1010 and antioxidant 168 in a mass ratio of 1:2.
[0093] The resulting POE composition had a limiting oxygen index (LOI) of 31.
[0094] Example 7
[0095] (1) Preparation of modified attapulgite:
[0096] A plasma reactor was used, oxygen was used as the processing gas; the reaction power was 70 watts, the processing time was 35 minutes, and the gas flow rate was 50 ml / minute, to modify the attapulgite to obtain modified attapulgite.
[0097] (2) Compounding of modified attapulgite and other flame retardants:
[0098] 15 parts by mass of the modified attapulgite and 2 parts by mass of graphene obtained in step (1) are modified with 0.35 parts by mass of methyl hydrogen silicone oil, and then mixed with 10 parts by mass of ammonium polyphosphate, 7 parts by mass of chitosan, 9 parts by mass of nano-magnesium hydroxide, and 0.7 parts by mass of titanate coupling agent bis(dioctylpyrophosphate)ethylene titanate to obtain a composite flame retardant material matrix.
[0099] (3) Blending of compound flame retardant material matrix and POE base material:
[0100] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 225° C. for granulation to obtain a flame retardant POE composition. 1.5 parts by mass of the light stabilizer 2-hydroxy-4-n-octyloxybenzophenone, 90 parts by mass of the POE base material, and 0.3 parts by mass of a composite antioxidant formed by the antioxidant 1076 and the antioxidant 168 in a mass ratio of 1:1.5 are added to the composite antioxidant.
[0101] The resulting POE composition had a limiting oxygen index (LOI) of 29.
[0102] Example 8
[0103] (1) Preparation of modified attapulgite:
[0104] A plasma reactor was used, oxygen was used as the processing gas; the reaction power was 75 watts, the processing time was 45 minutes, and the gas flow rate was 45 ml / minute, and the attapulgite was modified to obtain modified attapulgite.
[0105] (2) Compounding of modified attapulgite and other flame retardants:
[0106] 12 parts by mass of the modified attapulgite obtained in step (1) and 1 part by mass of graphene are modified with 0.3 parts by mass of methylhydroxy silicone oil, and then mixed with 8 parts by mass of ammonium polyphosphate, 9 parts by mass of chitosan, 9 parts by mass of nano-magnesium hydroxide, and 0.7 parts by mass of aluminate coupling agent triethyl aluminate to obtain a composite flame retardant material matrix.
[0107] (3) Blending of compound flame retardant material matrix and POE base material:
[0108] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 225° C. for granulation to obtain a flame retardant POE composition. The composite flame retardant material matrix obtained in step (2) is mixed with 1 part by mass of a light stabilizer 2-hydroxy-4-n-octyloxybenzophenone, 1 part by mass of 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 125 parts by mass of a POE base material, and 0.3 parts by mass of a composite antioxidant formed by an antioxidant 1076 and an antioxidant 626 in a mass ratio of 1:2.
[0109] The resulting POE composition had a limiting oxygen index (LOI) of 31.
[0110] Example 9
[0111] (1) Preparation of modified attapulgite:
[0112] A plasma reactor was used, oxygen was used as the processing gas; the reaction power was 100 watts, the processing time was 40 minutes, and the gas flow rate was 20 ml / minute, to modify the attapulgite to obtain modified attapulgite.
[0113] (2) Compounding of modified attapulgite and other flame retardants:
[0114] 10 parts by mass of the modified attapulgite and 4 parts by mass of graphene obtained in step (1) are modified with 0.35 parts by mass of methylhydroxy silicone oil, and then mixed with 8 parts by mass of ammonium polyphosphate, 9 parts by mass of chitosan, 9 parts by mass of nano-magnesium hydroxide, and 1 part by mass of an aluminate coupling agent tribenzyl aluminate to obtain a composite flame retardant material matrix.
[0115] (3) Blending of compound flame retardant material matrix and POE base material:
[0116] The composite flame retardant material matrix obtained in step (2) and 1 part by mass of light stabilizer 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole, 125 parts by mass of POE base material, and 0.3 parts by mass of a composite antioxidant formed by antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1.5 are added into a twin-screw extruder at 225° C. for granulation to obtain a flame retardant POE composition.
[0117] The resulting POE composition had a limiting oxygen index (LOI) of 30.
[0118] Example 10
[0119] (1) Preparation of modified attapulgite:
[0120] A plasma reactor was used, oxygen was used as the processing gas; the reaction power was 80 watts, the processing time was 40 minutes, and the gas flow rate was 35 ml / minute, to modify the attapulgite to obtain modified attapulgite.
[0121] (2) Compounding of modified attapulgite and other flame retardants:
[0122] 10 parts by mass of the modified attapulgite and 3 parts by mass of graphene obtained in step (1) are modified with 0.3 parts by mass of methylhydroxy silicone oil, and then mixed with 6 parts by mass of ammonium polyphosphate, 9 parts by mass of chitosan, 6 parts by mass of nano magnesium hydroxide, and 0.7 parts by mass of an aluminate coupling agent isopropyl distearate acyloxyaluminate to obtain a composite flame retardant material matrix.
[0123] (3) Blending of compound flame retardant material matrix and POE base material:
[0124] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 225° C. for granulation to obtain a flame retardant POE composition. 0.8 mass parts of the composite flame retardant material matrix obtained in step (2) and 0.3 mass parts of a composite antioxidant formed by light stabilizer 2-hydroxy-4-n-octyloxybenzophenone, 125 mass parts of a POE base material, and an antioxidant 1076 and an antioxidant 626 in a mass ratio of 1:1.5 are added to the composite antioxidant.
[0125] The resulting POE composition had a limiting oxygen index (LOI) of 30.
[0126] Embodiment 11
[0127] (1) Preparation of modified attapulgite:
[0128] A plasma reactor was used, oxygen was used as the processing gas; the reaction power was 80 watts, the processing time was 40 minutes, and the gas flow rate was 35 ml / minute, to modify the attapulgite to obtain modified attapulgite.
[0129] (2) Compounding of modified attapulgite and other flame retardants:
[0130] 10 parts by mass of the modified attapulgite and 3 parts by mass of graphene obtained in step (1) are modified with 0.3 parts by mass of methylhydroxy silicone oil, and then mixed with 6 parts by mass of ammonium polyphosphate, 9 parts by mass of chitosan, 6 parts by mass of nano magnesium hydroxide, and 0.7 parts by mass of an aluminate coupling agent isopropyl distearate acyloxyaluminate to obtain a composite flame retardant material matrix.
[0131] (3) Blending of compound flame retardant material matrix and POE base material:
[0132] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 225° C. for granulation with 0.8 parts by mass of light stabilizer 2-hydroxy-4-n-octyloxybenzophenone, 125 parts by mass of POE base material, and 0.3 parts by mass of antioxidant 1076 to obtain a flame retardant POE composition.
[0133] The resulting POE composition had a limiting oxygen index (LOI) of 27.
[0134] Example 12
[0135] (1) Preparation of modified attapulgite:
[0136] A plasma reactor was used, oxygen was used as the processing gas; the reaction power was 80 watts, the processing time was 40 minutes, and the gas flow rate was 35 ml / minute, to modify the attapulgite to obtain modified attapulgite.
[0137] (2) Compounding of modified attapulgite and other flame retardants:
[0138] 10 parts by mass of the modified attapulgite and 3 parts by mass of graphene obtained in step (1) are modified with 0.3 parts by mass of methylhydroxy silicone oil, and then mixed with 6 parts by mass of ammonium polyphosphate, 9 parts by mass of chitosan, 6 parts by mass of nano magnesium hydroxide, and 0.7 parts by mass of an aluminate coupling agent isopropyl distearate acyloxyaluminate to obtain a composite flame retardant material matrix.
[0139] (3) Blending of compound flame retardant material matrix and POE base material:
[0140] The composite flame retardant material matrix obtained in step (2), 0.8 parts by weight of light stabilizer 2-hydroxy-4-n-octyloxybenzophenone, and 125 parts by weight of POE base material are added into a twin-screw extruder at 225° C. for granulation to obtain a flame retardant POE composition.
[0141] The resulting POE composition had a limiting oxygen index (LOI) of 26.
[0142] Embodiment 13
[0143] (1) Preparation of modified attapulgite:
[0144] A plasma reactor was used, oxygen was used as the processing gas; the reaction power was 70 watts, the processing time was 45 minutes, and the gas flow rate was 50 ml / minute, to modify the attapulgite to obtain modified attapulgite.
[0145] (2) Compounding of modified attapulgite and other flame retardants:
[0146] 12 parts by mass of the modified attapulgite obtained in step (1) and 0.5 parts by mass of graphene are modified with 0.6 parts by mass of methyl silicone oil, and then mixed with 10 parts by mass of ammonium polyphosphate, 12 parts by mass of chitosan, 6 parts by mass of nano magnesium hydroxide, and 0.6 parts by mass of titanate coupling agent bis(dioctyloxypyrophosphate)ethylene titanate to obtain a composite flame retardant material matrix.
[0147] (3) Blending of compound flame retardant material matrix and POE base material:
[0148] The composite flame retardant material matrix obtained in step (2) and 0.8 parts by mass of light stabilizer 2'-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 120 parts by mass of POE base material, and 0.3 parts by mass of a composite antioxidant formed by antioxidant 1076 and antioxidant 168 in a mass ratio of 1:2 are added into a twin-screw extruder at 210° C. for granulation to obtain a flame retardant POE composition.
[0149] The resulting POE composition had a limiting oxygen index (LOI) of 30.
[0150] Comparative Example 1
[0151] The difference from Example 10 is that graphene is not added.
[0152] (1) Preparation of modified attapulgite:
[0153] A plasma reactor was used, oxygen was used as the processing gas; the reaction power was 80 watts, the processing time was 40 minutes, and the gas flow rate was 35 ml / minute, to modify the attapulgite to obtain modified attapulgite.
[0154] (2) Compounding of modified attapulgite and other flame retardants:
[0155] 10 parts by mass of the modified attapulgite obtained in step (1) is modified with 0.3 parts by mass of methylhydroxy silicone oil, and then mixed with 6 parts by mass of ammonium polyphosphate, 9 parts by mass of chitosan, 6 parts by mass of nano magnesium hydroxide, and 0.7 parts by mass of an aluminate coupling agent isopropyl distearate acyloxyaluminate to obtain a composite flame retardant material matrix.
[0156] (3) Blending of compound flame retardant material matrix and POE base material:
[0157] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 225° C. for granulation to obtain a flame retardant POE composition. 0.8 mass parts of the composite flame retardant material matrix obtained in step (2) and 0.3 mass parts of a composite antioxidant formed by light stabilizer 2-hydroxy-4-n-octyloxybenzophenone, 125 mass parts of a POE base material, and an antioxidant 1076 and an antioxidant 626 in a mass ratio of 1:1.5 are added to the composite antioxidant.
[0158] The resulting POE composition had a limiting oxygen index (LOI) of 23.
[0159] Comparative Example 2
[0160] The difference from Example 10 is that the addition amount of modified attapulgite is reduced from 10 parts by mass to 7 parts by mass.
[0161] (1) Preparation of modified attapulgite:
[0162] A plasma reactor was used, oxygen was used as the processing gas; the reaction power was 80 watts, the processing time was 40 minutes, and the gas flow rate was 35 ml / minute, to modify the attapulgite to obtain modified attapulgite.
[0163] (2) Compounding of modified attapulgite and other flame retardants:
[0164] 7 parts by mass of the modified attapulgite and 3 parts by mass of graphene obtained in step (1) are modified with 0.3 parts by mass of methylhydroxy silicone oil, and then mixed with 6 parts by mass of ammonium polyphosphate, 9 parts by mass of chitosan, 6 parts by mass of nano magnesium hydroxide, and 0.7 parts by mass of an aluminate coupling agent isopropyl distearate acyloxyaluminate to obtain a composite flame retardant material matrix.
[0165] (3) Blending of compound flame retardant material matrix and POE base material:
[0166] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 225° C. for granulation to obtain a flame retardant POE composition. 0.8 mass parts of the composite flame retardant material matrix obtained in step (2) and 0.3 mass parts of a composite antioxidant formed by light stabilizer 2-hydroxy-4-n-octyloxybenzophenone, 125 mass parts of a POE base material, and an antioxidant 1076 and an antioxidant 626 in a mass ratio of 1:1.5 are added to the composite antioxidant.
[0167] The resulting POE composition had a limiting oxygen index (LOI) of 25.
[0168] Comparative Example 3
[0169] The difference from Example 10 is that methylhydroxysilicone oil is not added.
[0170] (1) Preparation of modified attapulgite:
[0171] A plasma reactor was used, oxygen was used as the processing gas; the reaction power was 80 watts, the processing time was 40 minutes, and the gas flow rate was 35 ml / minute, to modify the attapulgite to obtain modified attapulgite.
[0172] (2) Compounding of modified attapulgite and other flame retardants:
[0173] 10 parts by mass of the modified attapulgite obtained in step (1), 3 parts by mass of graphene, 6 parts by mass of ammonium polyphosphate, 9 parts by mass of chitosan, 6 parts by mass of nano-magnesium hydroxide, and 0.7 parts by mass of an aluminate coupling agent isopropyl distearate acyloxyaluminate are mixed to obtain a composite flame retardant material matrix.
[0174] (3) Blending of compound flame retardant material matrix and POE base material:
[0175] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 225° C. for granulation to obtain a flame retardant POE composition. 0.8 mass parts of the composite flame retardant material matrix obtained in step (2) and 0.3 mass parts of a composite antioxidant formed by light stabilizer 2-hydroxy-4-n-octyloxybenzophenone, 125 mass parts of a POE base material, and an antioxidant 1076 and an antioxidant 626 in a mass ratio of 1:1.5 are added to the composite antioxidant.
[0176] The resulting POE composition had a limiting oxygen index (LOI) of 24.
[0177] Comparative Example 4
[0178] The difference from Example 10 is that the modified attapulgite is replaced by attapulgite, and the attapulgite is not subjected to a modification process.
[0179] (1) Compounding of attapulgite and other flame retardants:
[0180] 10 parts by mass of attapulgite and 3 parts by mass of graphene were modified with 0.3 parts by mass of methylhydroxy silicone oil, and then mixed with 6 parts by mass of ammonium polyphosphate, 9 parts by mass of chitosan, 6 parts by mass of nano magnesium hydroxide, and 0.7 parts by mass of aluminate coupling agent isopropyl distearate acyloxyaluminate to obtain a composite flame retardant material matrix.
[0181] (2) Blending of compound flame retardant material matrix and POE base material:
[0182] The composite flame retardant material matrix obtained in step (1) is added into a twin-screw extruder at 225° C. for granulation to obtain a flame retardant POE composition. The composite flame retardant material matrix obtained in step (1) is mixed with 0.8 parts by mass of light stabilizer 2-hydroxy-4-n-octyloxybenzophenone, 125 parts by mass of POE base material, and 0.3 parts by mass of a composite antioxidant formed by antioxidant 1076 and antioxidant 626 in a mass ratio of 1:1.5.
[0183] The resulting POE composition had a limiting oxygen index (LOI) of 23.
[0184] Comparative Example 5
[0185] The difference from Example 10 is that hexadecyltrimethylammonium bromide is used to modify the attapulgite.
[0186] (1) Preparation of modified attapulgite:
[0187] 4 g of attapulgite was added into 300 mL of deionized water and stirred to make it evenly dispersed, 3.42 g of hexadecyltrimethylammonium bromide was added and stirred, and the mixture was filtered and dried to obtain modified attapulgite.
[0188] (2) Compounding of modified attapulgite and other flame retardants:
[0189] 10 parts by mass of the modified attapulgite and 3 parts by mass of graphene obtained in step (1) are modified with 0.3 parts by mass of methylhydroxy silicone oil, and then mixed with 6 parts by mass of ammonium polyphosphate, 9 parts by mass of chitosan, 6 parts by mass of nano magnesium hydroxide, and 0.7 parts by mass of an aluminate coupling agent isopropyl distearate acyloxyaluminate to obtain a composite flame retardant material matrix.
[0190] (3) Blending of compound flame retardant material matrix and POE base material:
[0191] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 225° C. for granulation to obtain a flame retardant POE composition. 0.8 mass parts of the composite flame retardant material matrix obtained in step (2) and 0.3 mass parts of a composite antioxidant formed by light stabilizer 2-hydroxy-4-n-octyloxybenzophenone, 125 mass parts of a POE base material, and an antioxidant 1076 and an antioxidant 626 in a mass ratio of 1:1.5 are added to the composite antioxidant.
[0192] The resulting POE composition had a limiting oxygen index (LOI) of 25.
[0193] It can be seen from the results of the embodiments and comparative examples that the POE composition obtained by compounding graphene, modified attapulgite, silicone oil, chitosan, ammonium polyphosphate, nano-magnesium hydroxide, coupling agent, light stabilizer and POE base material has better flame retardant properties. In addition, it can be seen from the results of Example 10 and Comparative Examples 1 and 3 that without adding graphene or silicone oil, the flame retardant properties of the POE composition will be reduced, which can confirm that the components of the present invention play a synergistic role; from the results of Example 10 and Comparative Example 2, it can be seen that the amount of each component added will affect the flame retardant properties of the POE composition, and the POE composition obtained within the addition amount range of the present invention has better flame retardant properties; from the results of Example 10 and Comparative Example 4, it can be seen that if the attapulgite is used directly without modification, the flame retardant properties of the POE composition will be greatly reduced; from the results of Example 10 and Comparative Example 5, it can be seen that the flame retardant properties of the POE composition obtained by modifying the attapulgite with plasma are better than those by modifying the attapulgite with hexadecyltrimethylammonium bromide. This is because the modified attapulgite surface is rich in active groups such as hydroxyl and carboxyl groups through plasma modification, which is beneficial to the subsequent formation of the POE composition and improves the flame retardant properties of the POE composition.
[0194] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.
Claims
1. A POE composition, characterized in that The invention comprises the following components in parts by weight: 0.5-4 parts of graphene, 10-15 parts of modified attapulgite, silicone oil (accounting for 2-5% of the total weight of modified attapulgite and graphene), 8-12 parts of chitosan, 5-10 parts of ammonium polyphosphate, 5-10 parts of nano magnesium hydroxide, 0.5-1 parts of coupling agent, 0.5-2 parts of light stabilizer and 90-140 parts of POE base material.
2. The POE composition according to claim 1, characterized in that The flame retardant POE composition comprises: 0.8-2.5 parts of graphene, 11-14 parts of modified attapulgite, silicone oil (accounting for 2.5-4.0% of the mass ratio of modified attapulgite and graphene), 9-11 parts of chitosan, 6-9 parts of ammonium polyphosphate, 6-9 parts of nano magnesium hydroxide, 0.7-1 parts of coupling agent, 0.9-1.5 parts of light stabilizer and 110-130 parts of POE base material.
3. The POE composition according to claim 1, characterized in that The modified attapulgite is attapulgite that has been treated with plasma modification.
4. The POE composition according to claim 3, characterized in that The modified attapulgite is prepared by the following steps: adding attapulgite into a plasma reactor, inputting a treatment gas, and treating the attapulgite with electrons, free radicals, ions, and excited molecules in the plasma reactor to obtain the modified attapulgite.
5. The POE composition according to claim 4, characterized in that The processing gas includes but is not limited to at least one of oxygen, nitrogen, argon and methane.
6. The POE composition according to claim 4, characterized in that The power of the plasma reactor is 30-100 watts, the processing time is 10-50 minutes, and the flow rate of the processing gas is 20-60 ml / minute.
7. The POE composition according to claim 1, characterized in that The coupling agent is at least one of silanes, titanates and aluminates.
8. The POE composition according to claim 1, characterized in that The organic silicone oil is at least one of methyl silicone oil, methylethoxy silicone oil, methylvinyl silicone oil, methylhydroxy silicone oil, ethyl hydrogen silicone oil or hydroxy hydrogen silicone oil and methyl hydrogen silicone oil.
9. The POE composition according to claim 1, characterized in that The light stabilizer is at least one of a benzotriazole light stabilizer, a benzophenone light stabilizer, and a triazine light stabilizer.
10. The POE composition according to claim 1, characterized in that The POE base material has a melt index of 5-35 g / 10 min at 190°C and a load of 2.16 kg, and a density of 0.86-0.91 g / cm 3 .
11. The POE composition according to claim 1, characterized in that The invention also comprises an antioxidant, wherein the antioxidant is added in an amount of 0.1 to 3 parts by weight.
12. The POE composition according to claim 11, characterized in that The antioxidant is selected from antioxidant 1010, antioxidant 1076, antioxidant 168, antioxidant 626 and compound antioxidants thereof.
13. The POE composition according to claim 12, characterized in that The antioxidant is a composite antioxidant, wherein the main antioxidant of the composite antioxidant is antioxidant 1010 or antioxidant 1076, and the auxiliary antioxidant is antioxidant 168 or antioxidant 626; wherein the mass ratio of the main antioxidant to the auxiliary antioxidant is 1:1-1:
2.
14. A method for preparing the POE composition according to any one of claims 1 to 13, characterized in that: The following steps are involved: Step 1: Modify the modified attapulgite and graphene with silicone oil, then add ammonium polyphosphate, chitosan, nano magnesium hydroxide and a coupling agent to mix to obtain a composite flame retardant material matrix; Step 2: Add the compounded flame retardant material matrix, light stabilizer, POE base material and antioxidant into an extruder for mixing, and obtain a POE composition after extrusion.
Citation Information
Patent Citations
Intumescent flame retardant polyethylene containing organosilicon compound
CN101948581B
Thermoplastic polyester elastomer flame retardant composition and its preparation method
CN106947223B
Magnesium hydroxide / graphene sheet composite flame retardant and preparation method thereof
CN110423379A
Oil-resistant low-smoke halogen-free flame-retardant flexible polyurethane cable material and preparation method thereof
CN111647265A
Halogen-free flame retardant POE material and preparation method thereof
CN104140586A